Micronutrients Concentrations in Leaves of Oil Palm Trees Fertilized with Phosphorus, Potassium, and Magnesium - Viegas, Ismael de Jesus Matos; Costa, Milton Garcia; Ferreira, Eric Victor de Oliveira; Lima, Eduardo do Valle; Júnior, Mário Lopes da Silva; Silva, Dioclea Almeida Seabra (Journal of Agricultural Studies, 2021)
The management of micronutrients in oil palm trees in the Brazilian Amazon is still underdeveloped; thus, information on plant demands and their interactions with other nutrients is required to create adequate management procedures. The objective this work was to evaluate the effects of phosphate, potassium, and magnesium fertilization on micronutrient concentrations in leaves of oil palm trees. The experiment was carried out in the Brazilian Amazon in a randomized block design in a 4 x 2 x 3 x 2 factorial scheme, using four phosphorus levels, two phosphorus sources (natural phosphate and triple superphosphate), three potassium levels and two magnesium levels. Phosphate fertilization increased the concentrations of boron, chlorine, and iron in leaves, while copper and manganese concentrations in leaves decreased with increased doses of phosphorus. Among the phosphorus sources, triple superphosphate provided higher chlorine concentrations in leaves. Potassium fertilization increased only chlorine concentrations in leaves, while magnesium supply did not alter micronutrient concentrations in leaves. Thus, phosphorus and potassium fertilizers are essential to provide adequate micronutrient concentrations in leaves of oil palm trees.